2017
DOI: 10.22256/pubvet.v11n1.40-45
|View full text |Cite
|
Sign up to set email alerts
|

Mieloencefalitis protozoaria equina de evolución clínica aguda: Reporte de un caso

Abstract: A case of Equine Protozoal Myeloencephalitis caused by Sarcocystis neurona, was treated at the Veterinary Hospital of the Federal University of Lavras-MG. Among the neurological disorders in horses EPM is one of the most frequent and major economic losses in equideocultura. The animal in question showed symptoms acutely, with decubitus, reduction of superficial and deep skin sensitivity, loss of tail tone, facial nerve injury and urinary incontinence. The diagnosis was based on clinical symptoms, necropsy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Equine protozoan myeloencephalitis (EPM) had its first case reported in Brazil in Rio Grande do Sul, by Barros et al (1986) in a 10-years-old horse. Clinical case reports or studies investigating EPM have been reported in several Brazilian states (Masri et al, 1992;Lins et al, 2008;Faria et al, 2017). Henker et al (2020) concludes that EPM due to S. neurona infection represents an important neurologic disease of horses in Brazil and this disease should be considered as a main differential diagnosis in horses presenting neurologic signs.…”
Section: Introductionmentioning
confidence: 99%
“…Equine protozoan myeloencephalitis (EPM) had its first case reported in Brazil in Rio Grande do Sul, by Barros et al (1986) in a 10-years-old horse. Clinical case reports or studies investigating EPM have been reported in several Brazilian states (Masri et al, 1992;Lins et al, 2008;Faria et al, 2017). Henker et al (2020) concludes that EPM due to S. neurona infection represents an important neurologic disease of horses in Brazil and this disease should be considered as a main differential diagnosis in horses presenting neurologic signs.…”
Section: Introductionmentioning
confidence: 99%
“…Los equinos pueden ser afectados por enfermedades neurológicas infecciosas no contagiosas, entre la que se destaca la Mieloencefalitis Protozoaria Equina (sigla en inglés EPM = equine protozoal myeloencephalitis), llegando a producir disfunción neurológica encefálica y de médula espinal (Faria et al, 2017). La enfermedad es causada por los protozoarios Sarcocystis neurona, Neospora caninum y Neospora huguesi, siendo el Sarcocystis el patógeno de mayor diagnóstico en América (Teixeira et al, 2019).…”
Section: Introductionunclassified